Transient cauda equina syndrome: a subtle but sinister sign. (22nd March 2013) - Corns, Robert; Hasegawa, Harutomo; Jeffcote, Toby; Ashkan, Keyoumars
Abstract : A 54-year-old man presented with symptoms of cauda equina syndrome, which spontaneously resolved. Initial MRI did not show any compression of the cauda equine; however, an unusual pattern of epidural fat lead to further investigation and ultimately the diagnosis.